Optimization of nutrient requirement of Indian mustard (Brassica juncea L.) cultivars under poplar (Populus deltoides) based agroforestry system - Kaur, Ramandeep; Kaur, Navneet; Gill, R.I.S.; Sandhu, Sarabjot Kaur; Singh, Avtar (Indian Journal of Agroforestry, 2021)
Field experiments were done to determine optimum nutrient requirement of Indian mustard cultivars intercropped under three- and four-year old poplar block plantation at Bathinda and Ludhiana, Punjab respectively. Three cultivars of Indian mustard, namely Giriraj, RLC 3 and PBR 357 were intercropped under poplar with six nutrient levels viz., F0: control, F1: Zn25, F2: N75P22.5Zn25, F3: N100P30Zn25, F4: N125P37.5Zn25 and F5: N150P45Zn25 kg ha-1. Application of F5 significantly increased number of siliquae plant-1 (15.5 and 12.7%), number of seeds silique-1 (11.2 and 11.6%), seed (21.5 and 22.0%) and oil yield (18.9 and 19.8%) of Indian mustard cultivars than F3 at Ludhiana and Bathinda, respectively. Cultivar PBR 357 recorded highest seed yield (1293 and 1375 kg ha-1) and oil yield (513 and 543 kg ha-1) at Ludhiana and Bathinda, respectively. Cultivar PBR 357 with F5 application gave highest seed yield (1682 and 1800 kg ha-1 at Ludhiana and Bathinda, respectively) than other treatment combinations. Among nutrient levels, F2 (11.6 and 12.0 kg kg-1) and among cultivars, PBR 357 (10.3 and 10.9 kg kg-1) recorded highest nutrient use efficiency at Ludhiana and Bathinda, respectively. Highest agronomic efficiency (AE) of 3.7 kg kg-1 at both sites and physiological efficiency (PE) of 42.6 and 43.2 kg kg-1 at Ludhiana and Bathinda, respectively was obtained with F5. Cultivar Giriraj (3.7 kg kg-1) and PBR 357 (3.9 kg kg-1) showed highest AE at Ludhiana and Bathinda, respectively. Cultivar PBR 357 (42.1 kg kg-1) and Giriraj (41.1 kg kg-1) showed highest PE at Ludhiana and Bathinda, respectively. Highest apparent recovery (AR) of 44.5 and 45.3% at Ludhiana and Bathinda, respectively was obtained with F3. Cultivar RLC 3 (43.0%) and PBR 357 (44.5%) recorded highest AR at Ludhiana and Bathinda, respectively. Overall reduction in seed yield of Indian mustard was 17.2 and 20.4% under three- and four-year old poplar plantation than sole crop at Bathinda and Ludhiana, respectively.